Perspectives on Trends, Effectiveness, and Impediments to Prescribed Burning in the Southern U.S - Kobziar, Leda; Godwin, Daniel; Taylor, Leland; Watts, Adam (Forests, 2015)
The southern region of the U.S. uses prescribed fire as a management tool on more of its burnable land than anywhere in the U.S., with ecosystem restoration, wildlife habitat enhancement, and reduction of hazardous fuel loads as typical goals. Although the region performs more than 50,000 prescribed fire treatments each year, evaluation of their effects on wildfire suppression resources or behavior/effects is limited. To better understand trends in the use and effectiveness of prescribed fire, we conducted a region-wide survey of 523 fire use practitioners, working on both public and private lands. A 1–2 year prescribed fire interval was consistently viewed as effective in decreasing wildfire ignitions, behavior, and severity, as well as reducing suppression resources needed where wildfire occurred. Yet fewer than 15% of practitioners viewed burn intervals of 3–4 years as effective in reducing ignitions, underscoring the importance of high-frequency burning in vegetation communities where fuel recovery is rapid. Public lands managers identified limited budget and staffing as major institutional impediments to prescribed fire, in contrast to private individuals, more of whom chose liability as a key challenge. Differences in responses across ownership type, state, and vegetation type call for a broader perspective on how fire managers in the southern U.S. view prescribed fire.